KOMPLEKS CINDERELLA DALAM DIRI LILY BART DALAM NOVEL THE HOUSE OF MIRTH KARYA EDITH WHARTON - Ratna Asmarani (KAJIAN SASTRA, 2011)
This paper aims to analyze the problems of Cinderella Complex in Lily Bart, the young and single woman character in Edith Wharton’s The House of Mirth. The concepts used in the paper are Dowling’s concept of Cinderella Complex and Wolf’s concept of Victim Feminism. The result shows that it is difficult for a young, single, orphanated, penniless woman who has been internalized by Cinderella Complex to stand on her own and free herself from the snares of the high class life style which has been her little world so far. Key Words: Cinderella Complex, Victim Feminism, high class life style http://ejournal.undip.ac.id/index.php/kajiansastra/editor/submission/2916